2013
DOI: 10.1002/j.1532-2149.2013.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Communicating about opioids for chronic pain: A qualitative study of patient attributions and the influence of the patient–physician relationship

Abstract: Background: Chronic pain poses numerous challenges for patients and providers, particularly when opioid treatment is discussed. Despite accounts of antagonistic patient-provider communication, little is known about how communication about opioids unfolds during clinic visits and, importantly, how the relationship history of a patient and physician shapes this communication. This study's objective was to advance understanding of communication about opioid treatment by recording primary care clinic visits and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 43 publications
(46 reference statements)
3
75
0
1
Order By: Relevance
“…5 In a prior study (conducted in the same setting with different participants), we similarly found that many patients had positive beliefs about physicians' decisions to limit opioid use. 19 Patients often placed these decisions in the context of their physicians' past concern and support, attributing even disappointing decisions about opioids to their doctor's concern for their health. These findings lend support to recent arguments that the focus of opioid management should shift from detecting ''risky patients'' to managing ''risky drugs.''…”
Section: Discussionmentioning
confidence: 99%
“…5 In a prior study (conducted in the same setting with different participants), we similarly found that many patients had positive beliefs about physicians' decisions to limit opioid use. 19 Patients often placed these decisions in the context of their physicians' past concern and support, attributing even disappointing decisions about opioids to their doctor's concern for their health. These findings lend support to recent arguments that the focus of opioid management should shift from detecting ''risky patients'' to managing ''risky drugs.''…”
Section: Discussionmentioning
confidence: 99%
“…Because pain and opioid management are communicative activities and this communication is sometimes challenging, 2224,31 it is critical to learn more about how tapering occurs. These lessons learned will help to inform future clinical communication about tapering, to optimize patients’ understanding of and experiences with tapering, and to avoid unintended negative consequences.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when doctors showed genuine concern for their patients’ health and well-being, patients with chronic pain seemed more willing to accept decisions to limit or deny opioids. 22 In a recent study involving interviews with patients being tapered off of opioids, Frank and colleagues 13 reported that patients believed having a trusted physician was essential. Studies have shown that when patients and their PCPs have similar concerns about opioids, they can approach these concerns collaboratively.…”
Section: Discussionmentioning
confidence: 99%
“…These competing demands and time constraints decrease the time available to discuss pain concerns. 8,9 Third, self-management interventions in a healthcare setting frequently involve nurse care managers, pain psychologists, social workers, and other healthcare professionals who deliver self-management instruction and provide follow-up to patients, which allows for tailored delivery of relevant information. 7,10,11 However, such professionals are not always readily available in clinics, and individualized attention is resource intensive.…”
Section: Introductionmentioning
confidence: 99%